Patients’ preference for receiving healthcare services from out-of-area hospitals based on the Analytic Hierarchy Process (AHP): A mixed-methods study - Hosain Yasemi; Jamil Sadeghifar; Shahin Nargesi; Morteza Arab-Zozani; Khalil Momeni (PLoS ONE, 2026)
Introduction Meeting patients’ needs and expectations is one of the core responsibilities of healthcare delivery organizations in any region. Patients have two options for receiving services; either they go to hospitals outside their area of residence to receive medical services or they are referred by physicians to receive these services. Objective The present study aimed to identify and prioritize the factors influencing patients’ preference for obtaining healthcare services from out-of-area hospitals (Ilam Province). Methods This mixed study was conducted in two qualitative and quantitative phases in hospitals in Ilam city, 2024. In the qualitative phase, 15 experts and specialists were interviewed; data were collected using an In-depth interview guide and analyzed through a conventional content analysis approach. In the quantitative phase, 25 participants were assessed using a pairwise comparison questionnaire, and data were analyzed using the Analytical Hierarchy Process (AHP) with Expert Choice version 11. In the qualitative phase, Data analysis was conducted through employing the software MAXQDA-12. Results In the qualitative phase, the 41 identified subthemes were categorized into four main themes: physician-related factors, patient and family-related factors, service-providing organization–related factors, and sociocultural factors. Findings indicated that delayed payment of physicians’ claims, shortage of medical specialists, insufficient medical infrastructure and equipment, and promotional activities by healthcare centers in neighboring provinces played a key role in patient referral and preference for receiving healthcare services outside the province. According to the AHP results, physician-related factors were the most influential criteria, whereas sociocultural factors were the least significant in shaping patients’ preference for out-of-province hospitals. Conclusion Given the high annual referral rates and the substantial number of patients traveling outside the province to obtain medical services, health policymakers and provincial senior managers need to implement effective planning and corrective measures to reduce these referrals. Such measures may include recruiting the required specialists and subspecialists, developing practical strategies to improve retention of experienced physicians, enhancing medical equipment and infrastructure, and applying effective marketing strategies in the healthcare sector.